2020
DOI: 10.1101/2020.04.21.053488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structures of inactive and Gi-coupled GABAB heterodimer

Abstract: 22Metabotropic GABA B G protein-coupled receptor functions as a mandatory heterodimer of 23 GB1 and GB2 subunits and mediates inhibitory neurotransmission in the central nervous system. 24Each subunit is composed of the extracellular Venus flytrap (VFT) domain and transmembrane 25 (TM) domain. Here we present cryo-EM structures of human full-length heterodimeric GABA B 26 receptor in the antagonist-bound inactive state and in the active state complexed with agonist 27 and positive allosteric modulator in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Crystal structures of isolated mGluR1 (Wu et al, 2014) and mGluR5 (Dore et al, 2014, Christopher et al, 2019, Christopher et al, 2015 TMDs have shown TM1-mediated dimerization or monomers, respectively, while a cryogenic electron microscopy (cryo-EM) study of full-length mGluR5 (Koehl et al, 2019) showed no TMD interface in an inactive nanodisc-reconstituted form but a clear TM6 interface in a glutamate and positive allosteric modulator-bound pre-active state. Finally, a series of cryo-EM studies of the related GABA B receptors showed a lipid-mediated inactive TM5 interface that rearranged to a TM6 interface in the presence of agonist and a positive allosteric modulator (Mao et al, 2020, Papasergi-Scott et al, 2020, Park et al, 2020, Shaye et al, 2020. Together these studies point to a role for TMD rearrangement in mGluR activation, but the steps prior to formation of a putative active TM6 interface are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structures of isolated mGluR1 (Wu et al, 2014) and mGluR5 (Dore et al, 2014, Christopher et al, 2019, Christopher et al, 2015 TMDs have shown TM1-mediated dimerization or monomers, respectively, while a cryogenic electron microscopy (cryo-EM) study of full-length mGluR5 (Koehl et al, 2019) showed no TMD interface in an inactive nanodisc-reconstituted form but a clear TM6 interface in a glutamate and positive allosteric modulator-bound pre-active state. Finally, a series of cryo-EM studies of the related GABA B receptors showed a lipid-mediated inactive TM5 interface that rearranged to a TM6 interface in the presence of agonist and a positive allosteric modulator (Mao et al, 2020, Papasergi-Scott et al, 2020, Park et al, 2020, Shaye et al, 2020. Together these studies point to a role for TMD rearrangement in mGluR activation, but the steps prior to formation of a putative active TM6 interface are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clear effect of perturbing this interface and the subtype differences suggest that it may be a potential target for specific and potent drugs. Intriguingly, inter-TMD PAM and NAM binding has recently been observed in cryo-EM structures of GABABRs (Mao et al, 2020, Shaye et al, 2020, indicating that TMD interfaces may be druggable sites across family C GPCRs.…”
Section: Discussionmentioning
confidence: 95%
“…Crystal structures of isolated mGluR1 (Wu et al, 2014) and mGluR5 (Dore et al, 2014) TMDs have shown TM1-mediated dimerization or monomers, respectively, while a cryogenic electron microscopy (cryo-EM) study of full-length mGluR5 (Koehl et al, 2019) showed no TMD interface in an inactive nanodisc-reconstituted form but a clear TM6 interface in a glutamate and positive allosteric modulator-bound pre-active state. Finally, a series of cryo-EM studies of the related GABAB receptors showed a lipid-mediated inactive TM5 interface that re-arranged to a TM6 interface in the presence of agonist and a positive allosteric modulator (Mao et al, 2020, Papasergi-Scott et al, 2020, Park et al, 2020, Shaye et al, 2020). Together these studies point to a role for TMD rearrangement in mGluR activation, but the steps prior to formation of a putative active TM6 interface are not clear.…”
Section: Introductionmentioning
confidence: 99%